A correlation between grain boundary character and deformation twin nucleation mechanism in coarse-grained high-Mn austenitic steel - Chang-Yu Hung (Nature Portfolio, 2021)
Abstract In polycrystalline materials, grain boundaries are known to be a critical microstructural component controlling material’s mechanical properties, and their characters such as misorientation and crystallographic boundary planes would also influence the dislocation dynamics. Nevertheless, many of generally used mechanistic models for deformation twin nucleation in fcc metal do not take considerable care of the role of grain boundary characters. Here, we experimentally reveal that deformation twin nucleation occurs at an annealing twin (Σ3{111}) boundary in a high-Mn austenitic steel when dislocation pile-up at Σ3{111} boundary produced a local stress exceeding the twining stress, while no obvious local stress concentration was required at relatively high-energy grain boundaries such as Σ21 or Σ31. A periodic contrast reversal associated with a sequential stacking faults emission from Σ3{111} boundary was observed by in-situ transmission electron microscopy (TEM) deformation experiments, proving the successive layer-by-layer stacking fault emission was the deformation twin nucleation mechanism, different from the previously reported observations in the high-Mn steels. Since this is also true for the observed high Σ-value boundaries in this study, our observation demonstrates the practical importance of taking grain boundary characters into account to understand the deformation twin nucleation mechanism besides well-known factors such as stacking fault energy and grain size.